OP0076-HPR Effects of a soft thumb base splint in persons with carpometacarpal osteoarthritis: A randomised controlled trial. (23rd January 2014) - Hermann, M.; Nilsen, T.; Støyva Eriksen, C.; Haugen, I.; Christensen, B.S.; Kjeken, I.
Abstract : Background: Hand osteoarthritis (HOA) typically involves the distal interphalangeal joints the proximal interphalangeal joints, and the first carpometacarpal (CMC1) joint. Common functional consequences are pain, reduced hand mobility and grip force, and limitation in performance of daily activities. Carpometacarpal osteoarthritis (CMC1-OA) affect 5% of women over age 70 years and no disease-modifying intervention is available. Objectives: To assess the effectiveness, regarding pain, hand strength, function in daily activities of a prefabricated soft splint for persons with osteoarthritis of the CMC1-joint. Methods: In this randomised controlled trial, 59 persons with CMC1-OA were included. The control-group (n=29) received hand exercises and the splint-group (n=30) received hand exercises and splint. The following assessments were performed at baseline and after 2 months: Grip- and pinch strength in Newton (N) were measured with Grippit. Pain during resisted grip was measured on a numeric rating scale (NRS) (0=no pain). Thumb web-space was measured with Gripsize and joint mobility was recorded in millimetre (mm). Self-reported hand function was assessed with AUSCAN on five point Likert scales (0=no problem). Patients were recommended to perform hand exercises twice a day and the splint-group were instructed to wear the splint when having pain and/or when performing heavier manual tasks. At two months we also measured grip strength and pain both with and without splint in the splint-group and conducted a semi-structured interview were we asked splint-group about their experience with the splint. Results: The mean age of the participants was 70.5 years (SD 6.7), mean disease duration was 15.2 years, and one third had CMC-OA grade 3 or more. Nine participants were provided with a splint for their right thumb, 4 for left thumb and 17 participants for both thumbs. There were no significant differences between the groups in any outcome after two months. In the splint-group, pain during resisted grip was significant less when wearing the splint compared to without. Most participants were satisfied with the splint and reported the splint as useful, especially during household management. Conclusions: The results indicate that a soft prefabricated splint has an immediate pain- relieving when worn, but no long term effect in terms of reduced inflammation and pain, or improved strength or activity performance in patients with CMC1-OA. Disclosure of Interest: None Declared